ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL, LOAN TO DEPOSIT RATIO, DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS (Studi Empiris Pada Bank Umum Swasta Nasional Devisa yang terdaftar di Bursa Efek Indonesia Peri - Retta Oktaviana; Astrid Dita Meiriana Hakim (Universitas Budi Luhur, 2020)
This study aims to determine the effect of capital adequacy ratio, operational costs and operating income, loan to deposit ratio, and non-performing loans on return on assets in the national private foreign exchange banks listed on Indonesia Stock Exchange for the period 2014 - 2018. This study used fourteen samples of National Private Foreign Exchange listed Banks on the Indonesia Stock Exchange for the period 2014-2018. This study was conducted using panel data regression method with Fixed Effect Model from Econometric Views 10 Program and Calculated use Microsoft Excel 2010. The results showed that the capital adequacy ratio, operational costs and operating income, loan to deposit ratio, and non-performing loans have a significant effect on return on assets.